Functional Outcome of Titanium Elastic Nails for Diaphyseal Fracture of Humerus (Medical Forum Monthly, 2020)
Objective: To examine the functional outcomes of titanium elastic nails procedure in patients presented with diaphyseal fracture of humerus.Study Design: Retrospective/observational study.Place and Duration of Study: This study was conducted at the Orthopaedic and Trauma Surgery Department, Capital Hospital Islamabad from March 2019 to October 2019.Materials and Methods: Thirty patients of both genders with ages 18 to 60 years presented with diaphyseal fractures of humerus were included. Patients detailed were recorded after informed consent. All the fractures were treated with titanium elastic nailing. Clinical and radiological parameters were analyzed pre and postoperatively. Functional outcomes were analyzed by DASH scoring system. Post-operative complications were examined. Patients were followed for 6 months after surgery.Results: There were 24 (80%) male patients while 6 (20%) patients were females. Mean age of patients was 32.46±8.65 years. Road traffic accident was the most common mode of injury found in 19 (63.33%) patients. No patient had non-union. Mean union time was 2.84±1.15 months. 25 (83.33%) patients had excellent, 3 (10%) had good, 2 (6.67%) had fair and 0 patient with poor functional outcomes. 4 (13.33%) patients had postoperative complications, in which 2 patients had wound infection, 1 patient delayed union and 1 patient with elbow stiffness.Conclusion: Titanium elastic nail for duaphyseal fracture of humerus is safe and effective procedure with fewer rates of complications.